Clinician and patient experiences with shared decision-making to promote daily arm use for individuals with chronic stroke: an exploratory qualitative study - Gahlot, Amanda; Richardson, Grace; Librea, Patricia; Kim, Grace J. (Frontiers in Rehabilitation Sciences, 2024)
PurposeTo explore the attitudes and experiences of clinicians and individuals with chronic stroke on the use of shared decision-making (SDM) during upper extremity rehabilitation to improve daily arm use in the home environment. Specifically, we aimed to describe clinician and client perspectives regarding the facilitators and barriers to using SDM within the context of a self-directed upper extremity intervention for individuals living in the community with chronic stroke.MethodsData were collected within the context of an interventional study examining the feasibility of the Use My Arm-Remote intervention. Focus group interviews were conducted with the clinicians (n = 3) providing the intervention and individual semi-structured interviews with the participants (n = 15) of the study. All interview data were collected after the end of the intervention period. Data were analyzed using thematic analysis.ResultsThe following themes were identified: (1) Equal partnership; (2) Enhancing clinician confidence; and (3) This is different. Facilitators and barriers were identified within each theme. Key facilitators for clinicians were competence with SDM and patient characteristics; while facilitators for patients were open and trusting relationships with clinicians and personalized experience. Key barriers to SDM for clinicians were lack of expertise in SDM and participant buy in; while patients identified a lack of foundational knowledge of stroke rehabilitation as a potential barrier.ConclusionsKey barriers were analyzed using the consolidated framework for advancing implementation science to interpret results and identify strategies for enhancing the implementation of SDM in a virtual setting. The CFIR-ERIC tool highlighted the need for targeted educational meetings and materials to address the training and educational needs of both clinicians and patients for future iterations of this intervention.